Kekurangan Energi Kronik Pada Ibu Hamil Terhadap Kejadian Bayi Berat Lahir Rendah - Sri Utami Asmarani (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Low birth weight (LBW) is a baby who was born with a weight less than 2500 grams. The percentage of LBW in Indonesia was 10.2%, in West Java was 10.8% and Ciamis Regency was 4.8%. Lumbung Public Health Center is the Public Health Center with the highest number of LBW in Ciamis Regency. The birth weight of the baby is influenced by the state of the nutritional status of the pregnant women. One of the nutritional problems for pregnant women at Lumbung Public Health Center is chronic energy deficiency (CDC). The purpose of this research is to determine the relationship between chronic energy deficiency (CDC) in pregnant women with the occurrence of low birth weight babies (LBW) in the working area Lumbung Public Health Center, Ciamis Regency in 2017. This study used an analytical research design with a cross-sectional approach. The data were collected primary data and secondary data. The population in this study were all mothers who had babies in the working area of Lumbung Public Health Center as many as 487 and a sample of 165 mothers who had babies aged 0-6 months, this number was based on the sampling technique for different proportions. Data were analyzed using chi-square test. The results of the study were seen from the p-value of 0,000, meaning that there was a significant relationship between CED in pregnant women and the incidence of LBW. Health workers, especially midwifes who work in the work area of Lumbung Public Health Center to increase the extension program related to CDC, LBW and monitor upper arm circumference when the mother checks for the first time their pregnancy, so it can be known early on the abnormalities related to nutritional status and effort of the prevention. Keywords: chronic energy deficiency; pregnant women; low birth weight ABSTRAK Bayi berat lahir rendah (BBLR) adalah bayi yang lahir dengan berat badan kurang dari 2500 gram. Persentase BBLR di Indonesia sebesar 10,2%, di Jawa Barat sebesar 10,8% dan Kabupaten Ciamis sebesar 4,8%. Puskesmas Lumbung merupakan Puskesmas dengan jumlah BBLR tertinggi di Kabupaten Ciamis. Berat badan bayi yang dilahirkan dipengaruhi oleh keadaan status gizi ibu hamil. Salah satu masalah gizi pada ibu hamil di Puskesmas Lumbung adalah kekurangan energi kronik (KEK). Tujuan penelitian ini adalah mengetahui hubungan kekurangan energi kronik (KEK) pada ibu hamil dengan kejadian bayi berat lahir rendah (BBLR) di wilayah kerja Puskesmas Lumbung Kabupaten Ciamis tahun 2017. Penelitian ini menggunakan rancangan penelitian analitik dengan pendekatan cross-sectional. Data yang diambil adalah data primer dan data sekunder. Populasi pada penelitian ini adalah semua ibu yang memiliki bayi di wilayah kerja Puskesmas Lumbung sebanyak 487 dan sampel sebanyak 165 ibu yang memiliki bayi usia 0-6 bulan, jumlah tersebut berdasar rumus penghitungan sampel untuk beda proporsi. Data dianalisis menggunakan uji Chi-square. Hasil penelitian menunjukan bahwa nilai p = 0,000, artinya ada hubungan yang signifikan antara KEK pada ibu hamil dengan kejadian BBLR. Petugas kesehatan terutama bidan yang bertugas di wilayah kerja Puskesmas Lumbung harus lebih meningkatkan program penyuluhan terkait KEK, BBLR dan melakukan pemantauan lingkar lengan atas (LILA) pada saat pertama kali ibu memeriksakan kehamilannya. Sehingga dapat diketahui secara dini kelainan-kelainan yang berkaitan dengan status gizi dan upaya penanggulangannya. Kata kunci: kekurangan energi kronik; ibu hamil; bayi berat lahir rendah